Mannan-Based Nanodiagnostic Agents for Targeting Sentinel Lymph Nodes and Tumors - Jirátová, Markéta (Molecules, 2020)
Early detection of metastasis is crucial for successful cancer treatment. Sentinel lymph node (SLN) biopsies are used to detect possible pathways of metastasis spread. We present a unique non-invasive diagnostic alternative to biopsy along with an intraoperative imaging tool for surgery proven on an in vivo animal tumor model. Our approach is based on mannan-based copolymers synergistically targeting: (1) SLNs and macrophage-infiltrated solid tumor areas via the high-affinity DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin) receptors and (2) tumors via the enhanced permeability and retention (EPR) effect. The polymer conjugates were modified with the imaging probes for visualization with magnetic resonance (MR) and fluorescence imaging, respectively, and with poly(2-methyl-2-oxazoline) (POX) to lower unwanted accumulation in internal organs and to slow down the biodegradation rate. We demonstrated that these polymer conjugates were successfully accumulated in tumors, SLNs and other lymph nodes. Modification with POX resulted in lower accumulation not only in internal organs, but also in lymph nodes and tumors. Importantly, we have shown that mannan-based polymer carriers are non-toxic and, when applied to an in vivo murine cancer model, and offer promising potential as the versatile imaging agents.